2006
DOI: 10.1002/hup.817
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adjunctive antidepressant therapy with quetiapine on clinical outcome, quality of sleep and daytime motor activity in patients with treatment‐resistant depression

Abstract: Antidepressant treatment plus quetiapine is possibly a suitable treatment strategy to improve clinical depression, quality of sleep and motor activity. Future research is needed to understand the pharmacological interactions between antidepressants and quetiapine in major depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 28 publications
4
49
0
Order By: Relevance
“…Following data extraction 8 papers were excluded: 3 for having no interpretable data (Iverson, 2004;Ueda et al, 2005;Wolff, III et al, 1985), two conference abstracts with insufficient data (Deoras et al, 2010;Kelly et al, 2009), two for inappropriate comparisons (Lemke et al, 1998;Mendlowicz et al, 1999) and one as an exploratory study of non-linear dynamic measures of variability (Hauge et al, 2011). This left 19 papers from 16 studies suitable for detailed comparison Baune et al 2007;Berle et al, 2010;Coffield and Tryon, 2004;Faurholt-Jepsen et al, 2012;Foster et al, 1978;Glod et al 1992;Godfrey and Knight, 1984;Haynes et al, 2006;Joffe et al, 2009;Korszun et al, 2002;Raoux, 1994;Royant-Parola et al, 1986;Teicher et al, 1997;Todder et al, 2006;Todder et al, 2007;Volkers et al, 2002;Volkers et al, 2003;Winkler et al, …”
Section: Search Resultsmentioning
confidence: 99%
“…Following data extraction 8 papers were excluded: 3 for having no interpretable data (Iverson, 2004;Ueda et al, 2005;Wolff, III et al, 1985), two conference abstracts with insufficient data (Deoras et al, 2010;Kelly et al, 2009), two for inappropriate comparisons (Lemke et al, 1998;Mendlowicz et al, 1999) and one as an exploratory study of non-linear dynamic measures of variability (Hauge et al, 2011). This left 19 papers from 16 studies suitable for detailed comparison Baune et al 2007;Berle et al, 2010;Coffield and Tryon, 2004;Faurholt-Jepsen et al, 2012;Foster et al, 1978;Glod et al 1992;Godfrey and Knight, 1984;Haynes et al, 2006;Joffe et al, 2009;Korszun et al, 2002;Raoux, 1994;Royant-Parola et al, 1986;Teicher et al, 1997;Todder et al, 2006;Todder et al, 2007;Volkers et al, 2002;Volkers et al, 2003;Winkler et al, …”
Section: Search Resultsmentioning
confidence: 99%
“…Qualitative sleep studies using the Pittsburgh Sleep Quality Index (PSQI) have shown improvements in the sleep quality of depressed patients after initiation of quetiapine therapy. 23,24 The effect of quetiapine on sleep architecture, measured by PSG, has not been studied in patients experiencing a major depressive episode. Clinical practice indicates that quetiapine has sedating properties, and its sedative effects may play an important role in restoring quality of sleep in patients with MDD or bipolar disorder who frequently experience sleep disturbances as part of their illness.…”
mentioning
confidence: 99%
“…Three small studies reported remission rates of between 61-83% (Devarajan et al, 2006;Doree et al, 2007;Sagud et al, 2006) following 6-8 weeks of quetiapine addition to antidepressants. Larger studies have also showed reduction in depression measures following initiation of treatment with quetiapine and an antidepressant in treatment resistant patients and unipolar psychotically depressed patients (Baune et al, 2007;Konstantinidis et al, 2007). In this study, improvements in depression ratings following quetiapine administration were rapid.…”
Section: Discussionmentioning
confidence: 80%
“…Much interest has been generated in using quetiapine in depression following reports of an antidepressant effect in two randomised, placebo controlled trials in Bipolar Depression. Open-label studies of quetiapine augmentation in unipolar depression have also suggested benefits in patients with psychotic depression (Konstantinidis et al, 2007), treatment resistant depression (Baune et al, 2007;Devarajan et al, 2006;Sagud et al, 2006), adolescent major depression (Pathak et al, 2005) and patients with anxiety and depression (Adson et al, 2004). One small randomised study suggested superiority of quetiapine augmentation compared with lithium augmentation of antidepressants (Doree et al, 2007).…”
Section: Introductionmentioning
confidence: 95%